2016
DOI: 10.1089/jop.2016.0042
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Delivery of Timolol Maleate for Over 90 Days by Subconjunctival Injection

Abstract: A single subconjunctival administration of timolol microspheres achieved delivery and IOP reduction in rabbits for up to 90 days without local or systemic inflammation or toxicity. This approach has the potential to improve the management of glaucoma in patient populations, who are challenged to adhere to a regimen of daily eye drops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Injections and implants release drugs within the eye and may extend the release of drug up to several weeks or months [2,[19][20][21][22]. Biodegradable implants viz.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Injections and implants release drugs within the eye and may extend the release of drug up to several weeks or months [2,[19][20][21][22]. Biodegradable implants viz.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…These gels combine the benefits of solutions (accurate dosing) and gels (prolonged residence) for improved ocular bioavailability. pH-sensitive hydrogels with thermoresponsive properties, loaded with biodegradable polymer microspheres, present a novel ocular drug delivery system capable of prolonged glaucoma treatment 11 .…”
Section: Introductionmentioning
confidence: 99%
“…2,[5][6][7] To circumvent problems with topical eye drop therapies, there has been substantial effort in developing a sustained release formulation for glaucoma therapy. For example, delivery of timolol maleate or brimonidine tartrate has been explored in the forms of microspheres, [8][9][10] nanovesicles, 11 ocular inserts, 12 contact lenses, 13 and others. Furthermore, a recent study demonstrated that sustained release of dorzolamide by biodegradable microparticles not only reduced IOP in normotensive rabbits 14 but also decreased glaucomatous retinal ganglion cell loss in a rat disease model of glaucoma.…”
Section: Introductionmentioning
confidence: 99%